Programa de capacitação de cuidadores para o ensino de habilidades ocupacionais a adultos com deficiência intelectual - Silveira, Analice Dutra (2013)
The objective of this study was to investigate the effects of a teaching program for home caregivers of adults with intellectual disabilities who needed general support for teaching occupational skills to these adults. A multiple probe design was used. The study included three adults with intellectual disabilities, with ages ranging from 21 to 31 years, and 10 caregivers, with ages ranging from 19 to 78 years old. The study was divided into three phases. Phase I consisted of gathering information from caregivers to prepare the training program. Phase II sought to implement and evaluate the effects of the training program with caregivers. Phase III examined the effects of the intervention and a possible generalization of skills learned by participants in other environments. The training program was conducted in two phases that occurred simultaneously; theoretical training and practical training. In the theoretical training, it was presented to caregivers some theoretical frameworks that could assist them in teaching skills to adults with intellectual disabilities. In practical training the caregivers behaviors were modeled to favor learning skills by adults with intellectual disabilities. The results indicated that caregivers through systematic guidance were able to teach new behaviors to adults with intellectual disabilities in the context of daily activities. Moreover, the data suggest that adults with intellectual disabilities were also able to learn the behaviors necessary to perform the daily activities when appropriate teaching strategies were used.